Emotional challenges in the retail industry: Uncovering the role of emotional exhaustion in shop attendants' performance - Maulidiyah, Lia Al; Parahyanti, Endang (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Within the scope of the organization, performance is an important topic to be researched because of the facts that are crucial for the future and sustainability of the organization. To salesperson task performance are considered the most important and influential aspect in assessing their performance. In addition, emotional labor is known to be a display rule that is often found in front-line workers such as salesperson. So this study seeks to examine the relationship between emotional labor and task performance, through the mediating role of emotional exhaustion. Method: This study collected data from 58 participants who work as salesperson in the retail industry. The three instruments used in this study were the Emotional Labor Scale (ELS), the Maslach Burnout Inventory (MBI), and the Individual Work Performance Scale (IWPS). Result: The results showed that emotional exhaustion did not mediate the relationship between emotional labor (surface acting and deep acting) and task performance. Conclusion: However, the use of surface acting strategy is able to make retail salesperson experience higher exhaustion due to significant and positive relations. Novelty/Originality in this article: This study offers a new perspective in understanding the complex dynamics between emotional labor, emotional exhaustion, and task performance among retail salespeople. This study provides important insights into how psychological factors may influence job effectiveness in an industry that relies heavily on customer interactions.